Credit card minimum payment restrictions - Jason Allen; Michael Boutros; Benedict Guttman-Kenney (Bank of Canada, 2024)
We study a government policy that restricts repayment choices with the aim of reducing credit card debt. The policy requires the minimum payment on credit card balances in Quebec to be at least 2% of the statement balance for cards opened before August 2019 and at least 5% for cards opened after August 2019. The rest of Canada is unaffected. We estimate this policy's effects by applying a difference-in-differences methodology to comprehensive, Canadian consumer credit-reporting data. The policy causes a persistent increase in minimum payments. The policy has trade-offs: reducing revolving debt comes at a cost of reducing credit access, and potentially increasing delinquency.
Keywords: D18; E21; G28; G51; 330; Credit and credit aggregates; Financial system regulation and policies